Hydrochemical evaluation of groundwater quality and human health risk assessment of nitrate in the largest peninsula of China based on high-density sampling: A case study of Weifang. (1st November 2021) - Liu, Jiutan; Gao, Zongjun; Zhang, Yuqi; Sun, Zengbing; Sun, Tianzhu; Fan, Haibin; Wu, Bin; Li, Mingbo; Qian, Lili
Abstract: Groundwater is an important source of water, and the assessment of its hydrochemical characteristics, quality, and health risks is of great practical significance to ensure safe water use for residents and stable socioeconomic development. This study used high-density groundwater sampling data (1398 water samples) for Weifang to assess the groundwater quality and the health risks associated with drinking nitrate (NO3 − )-contaminated groundwater. The results indicated that the major chemical components of groundwater varied widely and had high coefficients of variation. The NO3 − concentration in groundwater ranged from 0.1 to 984 mg/L; it exceeded the Chinese standard groundwater quality threshold (88.57 mg/L) in 587 samples (41.99% of all samples). A Piper diagram indicated that the groundwater in Weifang is mainly of the SO4 ·Cl–Ca·Mg type and the HCO3 ·Ca·Mg type, and that groundwater with high NO3 − concentrations (>300 mg/L) is mainly of the SO4 ·Cl–Ca·Mg type. Hydrochemical analysis indicates that the groundwater chemistry in Weifang is mainly influenced by the weathering of silicate and carbonate rocks, cation exchange, and human activities. In addition, the NO3 − concentration in groundwater considerably influences its quality. The NO3 − concentration in the groundwater in Weifang is higher than that in many other regions of China, and is primarily attributed to agricultural activities. The calculated water quality index (WQI) shows that the groundwater in Weifang is mainly medium -quality water, but extremely poor -quality water is distributed extensively in some parts of the study region. The spatial distribution of the hazard quotient (HQ) is consistent with the spatial variation in groundwater NO3 − concentrations. Overall, the health risks associated with NO3 − in drinking water were greatest for infants, followed in decreasing order by children, teenagers, and adults.